Proton conducting composite membrane from sulfonated poly(ether ether ketone) and boron orthophosphate for direct methanol fuel cell application - Othman, M. H. D.; Ismail, Ahmad Fauzi; Mustafa, A. (Elsevier B.V., 2007)
A composite membrane for direct methanol fuel cell (DMFC) application was fabricated by blending sulfonated poly(ether ether ketone) (SPEEK) with boron orthophosphate (BPO4). The effects of the boron/phosphate (B/P) fraction of BPO4 and relative loading are discussed. These effects include membrane permeability to methanol and proton conductivity. The results showed that the proton conductivity of the composite membrane at room temperature increased with reduction of BPO4's B/P. However, the trade-off trend was exhibited in methanol permeability results. A 20 wt.% of BPO4 enhanced proton conductivity which deteriorated suddenly upon further loading. In comparison with Nafion® 117, the composite membranes have demonstrated better methanol separator property. The highest proton conductivity value of the composite membrane was 3.35 × 10−3 S/cm, and this value is adequate for DMFC application even though slighlty lower than the proton conductivity of Nafion® 117 membrane